Ectomycorrhizal response to bark beetle attack: a comparison of dead and surviving trees - Modlinger, Roman; Pešková, Vítězslava; Zelený, Jan; Macháčová, Markéta; Leiner, Martin; Tyšer, Daniel; Nakládal, Oto; Zumr, Václav; Surový, Peter (Frontiers in Forests and Global Change, 2025)
Bark beetle outbreaks have become increasingly prevalent and intense, causing widespread tree mortality and altering forest ecosystems globally. In this study, we investigate the dynamics between tree root systems of the Norway spruce and ectomycorrhizal fungi in the aftermath of bark beetle-induced tree mortality, focusing on the changes in density of vital and non-vital mycorrhizal tips. The survey was carried out in the Bohemian Switzerland National Park, Czechia. The sampling sites were chosen based on polygon layers delineating individual years of mortality status, obtained by PlanetLab imagery for 2018–2022, classified by Support Vector Machine, a machine learning tool (SVM). Fieldwork involved the collection of soil and root samples. Mycorrhizal tips were examined and counted using a stereomicroscope. Soil pH and root dry weight were determined. Wood decay fungi were identified using a comprehensive approach, combining macroscopic examination with genetic analysis. Due to the favorable conditions, the density of vital mycorrhizal tips (VM) on living trees gradually increased, peaking in the 2nd and 3rd years after the surrounding forest decay. VM on bark beetle snags was significantly lower compared to living trees, with minimal variation over time. The dry biomass of fine roots was significantly greater in living trees. Fine root abundance showed a slight decrease over time in living and dead trees; however, there was a lack of statistical significance. Most of the fine root biomass decomposes within the first half year after tree death. This might be influenced by wood decay fungi identified on dead trees, including genera Armillaria, Fomitopsis, and Pleurotus ostreatus. Overall, the study provides insights into the complex dynamics of mycorrhizal associations, root system biomass, and wood decay fungi in the aftermath of bark beetle-induced tree mortality. Our study demonstrates that mycorrhizal activity increases in trees surviving a bark beetle disturbance, and they probably become another ECM refugia. This research contributes valuable insights into the ecological consequences of bark beetle infestations on below-ground interactions, offering a deeper understanding of forest ecosystem responses to widespread tree mortality. Such knowledge is essential for developing effective strategies to manage and mitigate the ecological impacts of bark beetle outbreaks in forested environments.